Experimental and numerical investigation on water entry fluctuation effect of flared cavity. (June 2023) - Shi, Zhang; Duan, Wenyang; Huang, Zhenhua; Zhang, Gen; Jiang, Zhen; Huang, Limin
Highlights: The vertical water entry motion and load change law is explored, and the mechanism of the influence of gas expansion and contraction is revealed. Compared with the water entry of surface closed object, the flared cavity will generate a cyclic alternating load due to the repeated expansion and contraction of the gas in the cavity. As the air density in the cavity increases, the gas compresses and the pressure in the cavity increases; the air density in the cavity decreases, the gas expands and the pressure in the cavity decreases. Abstract: The water entry of flared cavity is a strong nonlinear process of multi-phase and multi domain coupling. In the process of liquid flowing into or out of flared cavity, there will be an obvious gas expansion and contraction in the cavity, which will not only lead to the bubble wall fluctuation, but also lead to the cyclic fluctuation of flared cavity's motion and load characteristics. In this study, a series of water entry tests of flared cavity were carried out, the fluctuation phenomenon of flared cavity during water entry was found, and their physical mechanism were revealed. Meanwhile, a hydrodynamic model is established to take into account the effect of gas pressure expansion and contraction, and a method of predicting the total pressure of flared cavity is proposed. The results show that: 1) During the water entry of flared cavity, the speed and pressure time history have obvious fluctuations effects, and the larger the water entry speed is, the more obvious the fluctuation effect is. 2) As the air density in the cavity increases, the gas compresses and the pressure in the cavity increases as well; Correspondingly, the air density in the cavity decreases, the gas expands and the pressure in the cavity decreases at the same time. 3) Compared with the surface closed objects, the water entry of flared cavity is affected not only by the hydrostatic pressure and dynamic pressure but also by the air pressure. Based on this rule, a prediction model (PMSP) of flared cavity's total pressure is proposed.